A review on dissimilar laser welding of steel-copper, steel-aluminum, aluminum-copper, and steel-nickel for electric vehicle battery manufacturing. (February 2022) - Sadeghian, Amirhossein; Iqbal, Naveed
Highlights: Review of the main challenges and scientific contributions. The relationship between the process parameters and joint properties are explored. The effect of intermetallic compounds on the joint properties is assessed. The applicability of interlayers and coatings are discussed. Opportunities for further research in this field are highlighted. Abstract: The electric vehicle (EV) battery systems are complex assemblies of dissimilar materials in which battery cells are connected using several thousand interconnect joints. Every single joint influences the functionality and efficiency of the whole battery system, making the joining process crucial. Laser welding is considered a desirable choice for EV battery manufacturing due to its non-contact nature, high energy density, precise control over the heat input, and ease of automation. However, incompatible thermos-physical properties of dissimilar materials used in battery tabs and interconnectors pose a significant challenge for achieving complete metallurgical bond. Furthermore, the formation of undesirable weld microstructures such as hard and brittle intermetallic compounds (IMCs) substantially undermines the structural, electrical, and thermal characteristics of battery joints. This paper reviews the fundamental difficulties and latest developments in dissimilar laser welding of steel-copper, steel-aluminum, aluminum-copper, and steel-nickel, some of the potential joint combinations in EV battery pack manufacturing. The weld microstructure and common metallurgical defects, as well as mechanical and electrical properties of joints are discussed. In addition, the effects of laser welding process parameters on the joint properties and the applicability of various interlayers and coatings in laser welding of battery materials are assessed.